A revision of the genus Armillipora Quate (Diptera: Psychodidae) with the descriptions of two new species – Corrigendum - Jaume-Schinkel, Santiago; Mengual, Ximo (European Journal of Taxonomy, 2024)
The present corrigendum rectifies issues in Jaume-Schinkel & Mengual (2024) https://doi.org/10.5852/ejt.2024.925.2459